2020
DOI: 10.1111/myc.13132
|View full text |Cite
|
Sign up to set email alerts
|

Fungal endocarditis in transplant recipients: A systematic review

Abstract: Summary Background Invasive fungal infections remain a major cause of morbidity and mortality in transplant recipients. Moreover, Fungal Infective Endocarditis (FIE) is a rare infection that carries a higher mortality than bacterial IE in normal host, while in transplant recipients may be even higher. The purpose of this study was to systemically review all published cases of FIE in solid organ and allogeneic bone marrow transplant recipients, describe the epidemiology, microbiology, clinical characteristics, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 86 publications
1
7
0
Order By: Relevance
“…However, in this study, the most common fungal cause of IE in patients with liver transplantation was Aspergillus spp. and the same is the case in other patients with organ transplantation [ 59 , 62 ]. Since the number of fungal IE in this study was small, these results should be addressed with caution.…”
Section: Discussionsupporting
confidence: 62%
“…However, in this study, the most common fungal cause of IE in patients with liver transplantation was Aspergillus spp. and the same is the case in other patients with organ transplantation [ 59 , 62 ]. Since the number of fungal IE in this study was small, these results should be addressed with caution.…”
Section: Discussionsupporting
confidence: 62%
“…Pergola et al found a higher occurrence of EE in Streptococcus bovis infections compared to other pathogens 32 . A recent systematic review of fungal endocarditis also reported a high embolic rate in patients infected by fungi 33 . Another study showed that infection with Staphylococcus spp .…”
Section: Predictors For Eementioning
confidence: 98%
“… Incidence of EE in fungal endocarditis: 62.5% in patients with kidney transplantation; 63.6% in patients with liver transplantation; 84.2% in patients with heart or lung transplantation 33 …”
Section: Predictors For Eementioning
confidence: 99%
“…Their participation in coinfection is very rare, but Nunez and colleagues reported simultaneous infections in an HIV-negative 69-year-old man with chronic obstructive pulmonary disease and type II diabetes mellitus [42]. Invasive pulmonary aspergillosis is a fungal disease strongly associated with immunocompromised patients [43]. Invasive pulmonary aspergillosis was reported in immunocompetent patients severely infected either with influenza B or influenza A H1N1 virus [44].…”
Section: Opportunistic Infections and Coinfectionmentioning
confidence: 99%